Development and economic and social rights: The Bretton Woods Institutions in Egypt post-2011 - El-Badrawi, Mahinour (AUC Knowledge Fountain, 2017)
Based on the hypothesis that there exists continuing tension between development and economic and social rights (ESR), where the latter end up principally skewed once they enter the development realm, this research explores why fields of development and ESR remain constantly at odds. Using Pierre Bourdieu’s theory of practice to define both fields and understand the continuous struggles and contradictions between them, this research argues there is a structural bias that leads to the struggle and always ends in favor of economic development targets at the expense of realization of ESR. The research begins by unpacking the development and ESR fields to understand the roots of the tension, and then moves on to study the struggle between ESR legal norms as they conflict with the founding principle of Bretton Woods development model. It continues by examining how those dynamics play out in the struggle between the contending demands for ESR realization and the economic development crisis in Egypt post-2011 revolution, which had economic and social right deprivations as a major root cause. This research opens the door for further study of how human rights can be realized despite the current structural bias in place by looking at the continuing struggles between the fields, the dominant doxas, and the limitations that play out once human rights enter the development habitus.